Selective magnetic nanographene oxide solid‐phase extraction with high‐performance liquid chromatography and fluorescence detection for the determination of zearalenone in corn samples - Thongprapai, Pornpimol; Cheewasedtham, Wilairat; K. F., Chong; Rujiralai, Thitima (WILEY-VCH Verlag, 2018)
A magnetic nanographene oxide sorbent as a selective sorbent for the magnetic solid‐phase extraction combined with high‐performance liquid chromatography and fluorescence detection was developed and proved to be a robust method for zearalenone determination in corn samples. Optimum extraction of zearalenone (20 mg magnetic nanographene oxide sorbent, extraction for 15 min, desorption time of 15 min using 1 mL of 0.5% formic acid in methanol) resulted in low limits of detection (05 mg/L) and quantitation (0.13 mg/L) and good linearity range of 0.13–1.25 mg/L with the correlation coefficient of 0.9957. Acceptable recoveries (79.3–80.6%) with relative standard deviations below 4% and satisfactory intra‐ and interday precisions (2–7.4%) were achieved. Additionally, the proposed method has been proved to be good in several aspects: easily prepared sorbent with high affinity to zearalenone, convenient and fast procedure, and high extraction efficiency.